Time Evolution of a Three-Body Wave Function in Two Dimensions - Rosa, D. S. [UNESP]; Yamashita, M. T. [UNESP]; Krein, G. [UNESP]; Jensen, A. S.; Orr, N. A.; Ploszajczak, M.; Marques, F. M.; Carbonell, J. (Springer, 2020)
In this article we study a three-body system in two dimensions formed by a light particle and two identical heavy dipoles in the Born-Oppenheimer approximation. We present the time evolution of the dipoles wave function using imaginary and real time propagation. In the first case we study the three-body ground state. In the second case the three-body system is a superposition of two different states. The time evolution shows that the tunneling of the wave function may be used to simulate a qubit.